Optimizing molecular light absorption in the strong coupling regime for solar energy harvesting. (July 2022) - Chavez, Steven; Linic, Suljo
Abstract: The strong coupling of optical absorbers (e.g., molecules or semiconductors) to confined photonic modes fundamentally alters the physical properties of the coupled system via the formation of hybrid light-matter states. One potential application of strong light-matter coupling relies on exploiting it to localize light-induced charge excitation processes to small volumes of material. Applications that would benefit from this localization include thin-film photovoltaics, photodetection, photocatalysis, and others, where the overall performance depends on the ability of a material to amplify light absorption (i.e., the formation of electron-hole pairs) within specific locations in space. This contribution investigates how strong light-matter coupling affects light absorption rates in molecular absorbers coupled to photonic nanostructures. Our results show that the molecular light absorption efficiencies are highest in configurations where the strongly coupled molecules interact directly with the incoming photon flux. We also identify a nonlinear dependence in the molecular absorption as a function of concentration, unique to the strongly coupled systems. Based on these results, we propose design principles for engineering nanostructured systems that allow for high efficiencies of charge carrier localization into strongly coupled absorbers. Graphical Abstract: ga1 Highlights: Strong coupling increases charge carrier generation rates in coupled molecular absorbers. Efficiencies are highest when the coupled molecules interact directly with incoming photons. Light absorption is nonlinear as a function of concentration in strongly coupled molecules.